Analysis of Rainfall Erosion and Protective Measures for the Aeolian Sand Subgrade Slope of the Wuma Expressway - Wenhua Yin; Fang Wang; Weizheng Liu; Yongxiang Wu; Xu Wang (Advances in Materials Science and Engineering)
It is difficult to build roads in the desert areas with wind-blown sands because the prevailing harsh environment and the characteristics of the aeolian sands inhibit strategies and measures for road damage prevention and control that are typically effective in other settings. Typically, the rainfall period in aeolian sand areas worldwide is concentrated and the rainfall volume is relatively large, which combined with small and unstable nature and the aeolian sand particles means roads built in these areas can be easily washed away and are vulnerable to water damage. Given geological conditions, topographic features and hydrometeorological conditions differ depending on the region, basic research into water damage in highway roadbed slopes in aeolian sand areas is necessary to formulate treatment measures that are versatile and applicable in different regions. Towards that end, this study strengthens the evaluation of roadbed and pavement drainage and protective measures given aeolian sand erosion caused by rainwater infiltration in certain longitudinal length sections of the Expressway K165 + 250 mileage pile section, and includes verification of the design scheme. The effects of rainwater drainage, storage, and subgrade reinforcement on the seepage and stability of drainage in a long longitudinal slope in the desert hinterland were quantitatively analyzed using numerical analysis. Additionally taking into account the regional climate environment characteristics that locally prevail, the necessity and applicability of geotechnical reinforcement in practical engineering applications is demonstrated. The research found the stability of the subgrade slope given potential for rainfall erosion due to concentrated-rainfall periods in an aeolian sand region is promoted through measures including slope drainage on the highway combined with side ditch drainage, strengthening of the box culvert under embankment ditches, and local protection by laying geogrid in the embankment to produce a significant lateral diffusion effect.